Blood pressure target attainment according to the recent ESC cardiovascular prevention guidelines. (11th May 2022) - Barkas, F; Koutsogianni, AD; Adamidis, P; Anastasiou, G; Liberopoulos, E; Liamis, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: New cardiovascular prevention guidelines have recently been issued by the European Society of Cardiology (ESC). Purpose: To record blood pressure (BP) target attainment according to the recent ESC cardiovascular prevention guidelines. Methods: A retrospective observational study involving 1334 dyslipidemic patients followed-up for ≥3 years at the Outpatient Lipid Clinic in University General Hospital of Ioannina, Greece. BP target attainment was recorded. ESC 2021 guidelines recommend a general target of BP <140/80 mmHg and individual targets of: i) diastolic BP <80 mmHg in all patients and ii) systolic BP 120-130 mmHg in patients 18-69 years of age without chronic kidney disease, or systolic BP 130-140 mmHg in patients 18-69 years of age with chronic kidney disease, or in those ≥70 years of age. Results: Among the 1334 subjects, 935 (45% men, 68 [60-75 years old]) were diagnosed with hypertension and received antihypertensive treatment. Of those, 19% were diagnosed with chronic kidney disease, 24% with atherosclerotic cardiovascular disease and 23% with type 2 diabetes. Of those, 75% were receiving an angiotensin receptor blocker, 52% a thiazide diuretic, 52% a calcium channel blocker, 37% a β-blocker, 13% an angiotensin converting enzyme inhibitor, 6% an aldosterone receptor blocker and 2% a centrally acting antihypertensive drug. Half of subjects had BP <140/80 mmHg, but only 21% achieved the individualized BP targets. Conclusions: A considerable proportion of hypertensive patients do not achieve target BP values.